2019
DOI: 10.23876/j.krcp.19.078
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes in kidney transplant recipients with renal cell carcinoma: a single-center study

Abstract: BackgroundPrevious studies have recommended a 2- to 5-year waiting time prior to kidney transplantation (KT) in patients with end-stage renal disease (ESRD) and symptomatic renal cell carcinoma (RCC) and no delay for incidental early-stage RCC. Data on Asian KT recipients are unavailable.MethodsThis is a Korean single-center retrospective study on 35 KT recipients with ESRD and RCC. Patients were classified into two groups: early KT (KT performed within 1 year after nephrectomy for RCC, including KT with simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the case we present, the right kidney tumor was not detected at first by ultrasound. Therefore, computed tomography and/or magnetic resonance imaging are often needed as further confirmatory examinations, especially for patients with the renal cystic disease ( 25 ).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…In the case we present, the right kidney tumor was not detected at first by ultrasound. Therefore, computed tomography and/or magnetic resonance imaging are often needed as further confirmatory examinations, especially for patients with the renal cystic disease ( 25 ).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…However, it has been advocated as RCC has been reported to be bilateral in 20% of ESRD patients. 17 Current pre-transplant screening recommendations for transplant candidates were typically not well validated. According to the European Renal Best Practice Transplantation Guidelines 18 , screening in ESRD patients is usually performed following the same protocols suggested for the general population.…”
Section: Rcc In Native Kidneysmentioning
confidence: 99%
“…The current guidelines for RCC also suggest that no delay is required for subjects with small or incidentally discovered RCC, while the recommendations for patients who have been treated for symptomatic RCC or for those with large or invasive tumors are conflicting. In this issue of Journal, Park et al [9] also reported that patients with early-stage and asymptomatic RCC did not require a mandatory observational period prior to kidney transplantation after curative nephrectomy.…”
mentioning
confidence: 99%